A borboleta azul na parede de vidro: o imaginário medieval em Nove, novena, de Osman Lins - Barbosa, Marta Maria Coêlho (2008)
The core of approach of the writer Osman Lins s lies in a restoration of the process of reconstructing the connection between the modern man to cosmos, applied to the called narratives abject, term of Walter Benjamin. That is because, when Middle Age allegory was rescued, Osman Lins constructs an interpretative way of this process that has as epicenter images of insects and animals, bases of the figurative metaphorical work of novels in analysis: Engagement, the Transparent Bird and Pentagon of Hahn and other narratives of Nine, Novena. In these, the sense of meaning emerges from the corrosion of relations between things that transform the living creatures into ruin, whose great effect is the loss of stability due to accumulation of information, in favor of the mutation dissection. The work of displacement of the language to the verbal communication makes Osman Lins s literary creation a way of domain the analogous words to the ones of the poetry, however in prose liberated by the allegory image. When making animals and insects a door of entrance to a world of mystery and fancy, also makes a constant investigation in histories of novels, established for the resignation to any mode of technology or totalitarian ideology applied to them. Tropo is a figure in libertarian use which occurs a transformation of allegory in image of contaminated novel Nine, Novena. The narratives in study are resultant of an attitude of rejection of the writer to stereotypes given to common-place in literary exercise, however dislocated by improvisation in a way to tell that it shows deformation and contamination under other affinities equivalents to the narrative statement: the objective is to return the identity to the language. The narrative representative work in Nine, Novena shows the man facing conflicts of modernity laid in cause of exploration to the meaning of abject, when stirring a reader up, by this means, to the reflection on automation, alienation and solitude, and, consequently, inaugurating a new time in Brazilian society in the second half of century XX: the word-animal making slit , new lives production in body-words.. The first chapter, Correlations of fragmentary narrative and the novel type, deals with the conceptual work of transformation and displacement of literal form of medieval allegory for a renowned and transfigured modality of Osman Lins s novel, in parallel to the illustration of Braque: Roofs of Céret. Second chapter, Allegorical confrontations: conceptual and artistic, it displays the visual descriptive and ornamental exercise in comparison to the illustration La Dame à La the Licorne, placing the medieval wonderful element in the motivation of the animal characters, personages in novels. The third chapter, Forms of ingenious concept: allegorical and metaphors, made possible the analysis of novels under the contamination of other visual symbols, pointing the distinguishing marks given by fragment and discursive contamination, for the poetical principles of analogy, comparison, irony, metaphorical and mosaic image plastic exhibitions methodologies and procedures of reading and interpretation. The conceptual recital if abided by the theoreticians: Walter Benjamin, Roland Barthes. Hansen, T. E. Hulme, Octávio Paz, Jaime Alazraki, Umberto Eco and readers Brazilian contemporaries of the workmanship of Osman Lins in preferential reference